Conductive interface modified sodium battery alloy foil negative electrode material as well as preparation method and application thereof
By preparing a conductive modification layer on the surface of the negative electrode of the sodium ion battery alloy foil, the problem of the alloy negative electrode material being prone to cracking and powdering during the cycle is solved, the conductivity and dynamic performance are significantly improved, and the effects of high specific capacity and high specific energy density are achieved.
Patent Information
- Application Number
- CN202311203885.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
The negative electrode material of sodium ion battery alloy is prone to cracking and powdering during the cycle, resulting in rapid attenuation of capacity and insufficient conductivity, which affects the current density and specific capacity.
By preparing a conductive modification layer on the bottom surface of the negative electrode of the sodium ion battery alloy foil, the conductive property of the foil is improved by using carbon-based conductive material coating or metal-based conductive material plating technology.
It significantly improves the conductivity and dynamic performance of the foil negative electrode material, can maintain high specific capacity and high specific energy density at a higher current density, and extends the cycling stability of the material.
Smart Images

Figure CN119650589A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium battery negative electrode, and in particular to a conductive interface modified sodium battery alloy foil negative electrode material and a preparation method and application thereof. Background Art
[0002] After more than 50 years of development, the performance and various indicators of sodium-ion batteries have become mature and stable. Continuing to improve the reversible specific capacity of positive and negative electrode materials of sodium-ion batteries remains the research focus and challenge in this field. At present, the negative electrode of sodium-ion batteries is mainly amorphous carbon materials, and the specific capacity has become mature. In order to further improve the energy density of sodium-ion battery cells, alloy negative electrode systems based on the principle of alloying reaction with sodium (such as tin, bismuth, antimony and other elements) are an important choice for the next generation of sodium-ion battery negative electrode materials.
[0003] Alloy negative electrode materials have a large volume expansion during the reaction (such as tin's volume expansion of 4.2 times), which is prone to cracking, pulverization and rapid capacity decay during the sodium ion battery cycle. At the same time, some alloy negative electrode materials are not compatible with mainstream carbonate system electrolytes, and some materials have poor kinetics that affect rate performance. This seriously hinders the manufacture and further application of alloy negative electrode materials. The development of sodium ion battery alloy negative electrode materials with higher specific capacity, excellent cycle performance and simple processing technology is one of the important challenges for the next generation of sodium ion batteries.
[0004] It is a very advanced concept to directly use alloy elements to make foil negative electrodes (such as metal single-element foils such as tin, bismuth, and antimony) as negative electrode active materials. A whole piece of metal foil can react with sodium to store sodium by alloying. Since the metal foil itself is a whole, it is equivalent to eliminating the binder and the current collector. Compared with the traditional negative electrode, it can achieve higher specific energy density, lower cost, higher compaction density, and eliminate the processing steps such as negative electrode cell mixing and homogenization, as well as convenient recycling, which has great application prospects. However, the surface load of the foil negative electrode is higher, and it needs to withstand a higher surface current density at the same charge and discharge rate, which poses a great challenge to the conductivity of the foil negative electrode. Especially for some foil negative electrodes made of metals with poor conductivity, such as Sn (tin), the problem of conductivity is particularly serious. Poor metal conductivity will lead to large polarization and low capacity of the foil negative electrode, and the advantages of high capacity and high specific energy density cannot be fully utilized. At present, there is no effective means to improve the conductivity of foil negative electrodes, which seriously affects the capacity during the cycle. For example, tin foil negative electrodes can only exert about 80% of the theoretical capacity (847 mAh / g) at a very small current density of 0.1 A / g, and the capacity activation cycle is relatively long, so the practical application of foil negative electrodes is far away. Therefore, if the interfacial conductivity of foil negative electrodes can be enhanced to bring about stronger overall kinetic performance, so that foil negative electrodes can adapt to higher current densities in practical applications and exert higher specific capacity, it will inevitably further promote the research and application of next-generation sodium-ion battery negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a conductive interface modified sodium battery alloy foil negative electrode material and its preparation method and application. The conductive interface modified sodium battery alloy foil negative electrode material of the present invention has high specific capacity and high surface loading, and can effectively improve the current density of the cycle through conductive interface modification. The material can be used for large-scale commercial preparation and application.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a conductive interface modified sodium battery alloy foil negative electrode material, the conductive interface modified sodium battery alloy foil negative electrode material comprising: a sodium ion battery alloy foil negative electrode and a conductive modification layer completely attached to the bottom surface of the sodium ion battery alloy foil negative electrode;
[0007] Wherein, the sodium ion battery alloy foil negative electrode is a foil material as a whole, does not contain a conductive agent or a binder inside, and is attached or not attached to a current collector on the surface;
[0008] The conductive modification layer includes a carbon-based conductive modification layer prepared by a coating process or a metal-based conductive modification layer prepared by a plating process;
[0009] The mass proportion of the conductive material in the conductive interface modified sodium battery alloy foil negative electrode material is less than 50%.
[0010] Preferably, the sodium ion battery alloy foil negative electrode is specifically: a foil made of a metal element, a foil made of an alloy of multiple metal elements, or a foil made of an alloy of one or more metal elements and one or more non-metallic elements;
[0011] The metal elements include: one or more of Sn, Sb, Bi, Ge, and Pb elements; the non-metal elements include: one or more of S, Se, and P elements.
[0012] Preferably, the carbon-based conductive modification layer prepared by the coating process includes: one or more of graphene, MXene, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerenes, carbon black, Ketjen black, graphite, hard carbon, and soft carbon with conductive properties.
[0013] Preferably, the metal-based conductive modification layer prepared by the plating process includes: one element or a composite of several elements selected from the group consisting of silver (Ag), copper (Cu), gold (Au), aluminum (Al), molybdenum (Mo), tungsten (W), zinc (Zn), cobalt (Co), nickel (Ni), iron (Fe), manganese (Mn) and platinum (Pt) having conductive properties.
[0014] In a second aspect, an embodiment of the present invention provides a method for preparing the conductive interface modified sodium battery alloy foil negative electrode material described in the first aspect, the preparation method comprising: preparing a conductive modification layer on the bottom surface of the sodium ion battery alloy foil negative electrode.
[0015] Preferably, the conductive modification layer prepared on the bottom surface of the negative electrode of the sodium ion battery alloy foil is: a carbon-based conductive modification layer prepared by a coating process;
[0016] Specifically, the method comprises: mixing a carbon-based conductive material and a binder according to a required mass ratio, uniformly dispersing the carbon-based conductive material with a solvent, forming a film on the negative electrode surface of a sodium ion battery alloy foil, and drying the dispersed solvent to obtain a surface of a negative electrode of a sodium ion battery alloy foil with a carbon-based conductive modified layer prepared by an attachment coating process and drying the surface; the solid content of the carbon-based conductive material accounts for 20% to 95% by weight; the rotation speed for uniformly dispersing the carbon-based conductive material with a solvent is 500 to 3000 rpm, and the dispersion time is 0.2 to 10 hours;
[0017] Among them, the specific process of forming the film on the surface of the negative electrode of the sodium ion battery alloy foil includes: one of: flat film cold roller, flat film cold tank, flat film co-extrusion, blown film or blown film co-extrusion.
[0018] Preferably, the conductive modification layer prepared on the bottom surface of the sodium ion battery alloy foil negative electrode is: a metal-based conductive modification layer prepared by a plating process;
[0019] Specifically, the method comprises: subjecting the required metal-based conductive target material to ion bombardment at a set voltage or evaporation and gasification at a set temperature or dissolution through an electrochemical oxidation reaction, and depositing a homogeneous coating on the surface of the negative electrode of the sodium ion battery alloy foil, wherein the coating thickness is 10-200 microns; and then drying, wherein the drying temperature is 60-150° C., and the drying time is 4-16 hours; and the thickness of the conductive modification layer after drying is 0.5-150 microns;
[0020] The specific process of preparing the metal-based conductive modification layer by the plating process includes: one of vacuum evaporation, sputtering, spraying, ion plating, electroplating, coating and chemical plating.
[0021] In a third aspect, an embodiment of the present invention provides a sodium ion battery negative electrode, comprising the conductive interface modified sodium battery alloy foil negative electrode material described in the first aspect above.
[0022] In a fourth aspect, an embodiment of the present invention provides a sodium ion battery, comprising the sodium ion battery negative electrode described in the third aspect above.
[0023] In a fifth aspect, an embodiment of the present invention provides an electronic device comprising the sodium ion battery described in the fourth aspect.
[0024] The conductive interface modified sodium battery alloy foil negative electrode material provided by the embodiment of the present invention. After being treated by a carbon-based conductive material coating or a metal-based conductive material plating process, the conductivity of the foil negative electrode material as a whole can be significantly improved without sacrificing the overall specific capacity of the foil negative electrode, thereby ensuring the capacity under different charge and discharge rates. After a current density of 0.2A / g or above, the specific capacity of the foil negative electrode material after conductive modification is significantly improved compared with the unmodified control sample. The carbon-based conductive material coating or metal-based conductive material plating process used in the conductive modification of the foil negative electrode material of the present invention has a simple process, mature technology, rich choices, low equipment requirements, low overall cost, and easy large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic structural diagram of a conductive interface modified sodium battery alloy foil negative electrode material provided in an embodiment of the present invention;
[0026] Figure 2 A surface scanning electron microscope (SEM) image of the material provided in Example 1 of the present invention;
[0027] Figure 3 The first cycle charge and discharge curve of the material provided in Example 1 of the present invention;
[0028] Figure 4 Provides a specific capacity / coulombic efficiency cycle diagram of the material at different rates for Example 1 of the present invention;
[0029] Figure 5 A surface SEM image of the material provided for Example 2 of the present invention;
[0030] Figure 6 The first cycle charge and discharge curve of the material provided for Example 2 of the present invention;
[0031] Figure 7 Provides a specific capacity / coulombic efficiency cycle diagram at different rates for Example 2 of the present invention;
[0032] Figure 8 The camera-generated real picture without magnification that provides materials for Example 3 of the present invention;
[0033] Fig. 9 A cross-sectional SEM image of the material is provided for Example 3 of the present invention;
[0034] Fig.10 The first cycle charge and discharge curve of the material provided in Example 3 of the present invention;
[0035] Fig.11 Provides a specific capacity / coulombic efficiency cycle diagram at different rates for Example 3 of the present invention;
[0036] Fig.12 The surface SEM image of the material after charge and discharge cycles provided in Example 3 of the present invention;
[0037] Fig.13 The surface SEM image of the material after charge and discharge cycles provided in Example 3 of the present invention;
[0038] Fig.14 The first cycle charge and discharge curve of the material provided for Example 4 of the present invention;
[0039] Fig.15 Provides a specific capacity / coulombic efficiency cycle diagram at different rates for Example 4 of the present invention;
[0040] Fig.16 The first cycle charge and discharge curve of the material provided in Example 5 of the present invention;
[0041] Fig.17 Provides a specific capacity / coulombic efficiency cycle diagram of the material at different rates for Example 5 of the present invention;
[0042] Fig.18 The first cycle charge and discharge curve of the material provided in Example 6 of the present invention;
[0043] Fig.19 Provides a specific capacity / coulombic efficiency cycle diagram at different rates for Example 6 of the present invention;
[0044] Fig. 20 The first cycle charge and discharge curve of the material provided in Example 7 of the present invention;
[0045] Fig.21 Provides a SEM image of the material for Comparative Example 1 of the present invention;
[0046] Fig. 22 The first-week charge-discharge curve of the material provided for Comparative Example 1 of the present invention;
[0047] Fig.23 Provides a specific capacity / coulombic efficiency cycle diagram of the material at different rates for comparative example 1 of the present invention;
[0048] Fig.24 The first-cycle charge-discharge curve of the material is provided for Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0050] The embodiment of the present invention provides a conductive interface modified sodium battery alloy foil negative electrode material, the structure of which is as follows Figure 1 As shown, the conductive interface modified sodium battery alloy foil negative electrode material comprises: a sodium ion battery alloy foil negative electrode 1 and a conductive modification layer 2 completely attached to the bottom surface of the sodium ion battery alloy foil negative electrode;
[0051] Among them, the sodium ion battery alloy foil negative electrode is a whole foil material, does not contain conductive agent, binder inside, and the surface is not attached to the current collector; the sodium ion battery alloy foil negative electrode is specifically: a foil made of a metal element, a foil made of an alloy of multiple metal elements, or a foil made of an alloy of one or more metal elements and one or more non-metallic elements; wherein the metal elements include: one or more of Sn, Sb, Bi, Ge, Pb elements; the non-metallic elements include one or more of S, Se, P elements.
[0052] The conductive modification layer includes a carbon-based conductive modification layer prepared by a coating process or a metal-based conductive modification layer prepared by a plating process; the mass proportion of the conductive material in the conductive interface modified sodium battery alloy foil negative electrode material is less than 50%.
[0053] The carbon-based conductive modification layer prepared by the coating process includes: one or more of graphene, MXene, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerenes, carbon black (acetylene black), Ketjen black, graphite, hard carbon, and soft carbon with conductive properties.
[0054] The metal-based conductive modification layer prepared by the plating process includes: one element or a combination of several elements selected from the group consisting of silver (Ag), copper (Cu), gold (Au), aluminum (Al), molybdenum (Mo), tungsten (W), zinc (Zn), cobalt (Co), nickel (Ni), iron (Fe), manganese (Mn) and platinum (Pt) with conductive properties.
[0055] The conductive interface modified sodium battery alloy foil negative electrode material of the present invention can be obtained by preparing a conductive modified layer on the bottom surface of the sodium ion battery alloy foil negative electrode.
[0056] The specific method may be to use a carbon-based conductive modification layer prepared by a coating process or a metal-based conductive modification layer prepared by a plating process.
[0057] The carbon-based conductive modification layer prepared by the coating process specifically includes: mixing the carbon-based conductive material and the binder according to the required mass ratio, uniformly dispersing them with a solvent, forming a film on the negative electrode surface of the sodium ion battery alloy foil, and drying the dispersed solvent to obtain the negative electrode surface of the sodium ion battery alloy foil with the carbon-based conductive modification layer prepared by the coating process attached. The thickness of the conductive modification layer formed after drying is 0.5-150 microns.
[0058] In the above conductive interface modified sodium battery alloy foil negative electrode material, the solid content of carbon-based conductive material accounts for 20%-95% by weight; the rotation speed of the uniform dispersion by the solvent is 500-3000rpm, and the dispersion time is 0.2-10 hours; wherein, the specific process of filming on the surface of the negative electrode of the sodium ion battery alloy foil includes: flat film cold roller (casting), flat film cold tank, flat film co-extrusion, blown film or blown film co-extrusion. Carbon-based conductive materials include one or more of graphene, MXene, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerenes, carbon black (acetylene black), Ketjen black, graphite, hard carbon, and soft carbon with conductive properties.
[0059] The metal-based conductive modification layer prepared by the coating process specifically includes: ion bombarding the required metal-based conductive target material at a voltage of 15V-10KV or high-temperature evaporation and gasification at 300-2600 degrees Celsius or electrochemical oxidation reaction dissolution under a vacuum degree of 0.1-15 Pa, and depositing a homogeneous coating on the surface of the negative electrode of the sodium ion battery alloy foil, with a coating thickness of 10-200 microns; then drying, the drying temperature is 60-150°C, and the drying time is 4-16 hours; the thickness of the conductive modification layer after drying is 0.5-150 microns;
[0060] Among them, the specific processes for preparing the metal-based conductive modification layer by the plating process include: vacuum evaporation, sputtering, spraying, ion plating (hollow cathode ion plating / hot cathode ion plating / arc ion plating / active reaction ion plating / radio frequency ion plating / DC discharge ion plating), electroplating (water plating or cold plating), coating (brush plating or tankless electroplating), and chemical plating.
[0061] The thickness of the conductive modified interface finally formed on the surface of the alloy foil negative electrode of the present invention is 0.5-150 microns, and the mass proportion of the conductive material in the alloy foil negative electrode after the conductive interface modification is less than 50%. This can significantly improve the conductivity of the foil negative electrode, enhance the overall dynamic performance of the foil negative electrode, reduce polarization, and promote the use of capacity. For example, the tin foil negative electrode after the interface conductive modification can exert about 98% of the theoretical capacity (theoretical capacity 847 mAh / g) at 0.1 amps / gram, and can achieve more than 80% of the theoretical capacity (theoretical capacity 847 mAh / g) at a current density of 0.5 amps / gram, achieving higher rate charge and discharge while ensuring high capacity and high specific energy density, and at the same time helping to dissipate the heat generated by charge and discharge, and improving high and low temperature performance.
[0062] The conductive interface modified sodium battery alloy foil negative electrode material provided by the embodiment of the present invention can be used as the negative electrode of a sodium ion battery, and the sodium ion electrode can be applied to electronic devices. The conductive interface modified sodium battery alloy foil negative electrode material of the present invention has a higher mass specific capacity at different current densities than the unmodified alloy foil negative electrode material.
[0063] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the conductive interface modified sodium battery alloy foil negative electrode material of the present invention are respectively described below with multiple specific examples.
[0064] Example 1
[0065] 4 g of carbon black and 6 g of sodium carboxymethyl cellulose were placed in a ball mill, 300 g of ball mill beads were added, 10 ml of a 1:1 mixed solution of deionized water and ethanol was added, and the mixture was stirred at 300 rpm for 1 hour. The slurry and the ball mill beads were separated, and the slurry was coated on the prepared 10-micron thick tin foil surface by a flat film cold roller process. The initial thickness of the slurry was 30 microns, and then transferred to an oven and dried at 80 degrees Celsius for 6 hours to obtain a tin foil negative electrode material with conductive modification on the carbon black surface; the thickness of the tin foil negative electrode after drying was about 12 microns. Figure 2 The surface scanning electron microscope (SEM) image of the material provided in Example 1 of the present invention. Due to the low density of carbon black and sodium carboxymethyl cellulose, the mass of the negative electrode of the tin foil in the subsequent comparative example 1 without surface conductivity modification is almost not significantly increased.
[0066] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME (ethylene glycol dimethyl ether) as the electrolyte. Glass fiber was used as the diaphragm to assemble the CR2032 button-type cell in an argon glove box. Figure 3 The first cycle charge and discharge curve of the material provided in Example 1 of the present invention is that the first cycle charge and discharge cycle is carried out at a voltage range of 0-1V and a current density of 0.1A / g to obtain a reversible specific capacity of 755mAh / g and a first cycle coulombic efficiency of 90.16%. Figure 4A specific capacity / coulombic efficiency cycle diagram at different rates of the material is provided for Example 1 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 ampere / gram, 0.2 ampere / gram, 0.5 ampere / gram, and 1 ampere / gram, respectively. Finally, a charge and discharge cycle is performed at a current density of 0.5 ampere / gram to obtain rate performance data of a tin foil negative electrode material with conductive surface modification of carbon black, wherein the reversible specific capacity at a current density of 0.2 ampere / gram is 798 mAh / gram, the reversible specific capacity at a current density of 0.5 ampere / gram is 675 mAh / gram, and the reversible specific capacity at a current density of 1 ampere / gram is 367 mAh / gram.
[0067] Example 2
[0068] 3 g of multi-walled carbon nanotubes and 6 g of sodium alginate were placed in a ball mill, 270 g of ball mill beads were added, 9 ml of a 1:1 mixed solution of deionized water and ethanol were added, and the mixture was stirred at 400 rpm for 1 hour. The slurry and the ball mill beads were separated, and the slurry was coated on the prepared 10-micron thick tin foil surface by a flat film cold roller process. The initial slurry thickness was 40 microns, and then transferred to an oven and dried at 80 degrees Celsius for 6 hours to obtain a tin foil negative electrode material with conductive modification on the surface of multi-walled carbon nanotubes; the thickness of the tin foil negative electrode after drying was about 12 microns. Figure 5 The surface SEM image of the material is provided for Example 2 of the present invention. Due to the low density of multi-walled carbon nanotubes and sodium alginate, the mass of the tin foil negative electrode without surface conductivity modification in Comparative Example 1 has almost no significant increase.
[0069] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Figure 6 The first cycle charge and discharge curve of the material provided in Example 2 of the present invention is that the first cycle charge and discharge cycle is carried out at a voltage range of 0-1V and a current density of 0.1A / g to obtain a reversible specific capacity of 755mAh / g and a first cycle coulombic efficiency of 89.90%. Figure 7 A specific capacity / coulombic efficiency cycle diagram at different rates of the material is provided for Example 2 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 ampere / gram, 0.2 ampere / gram, 0.5 ampere / gram, and 1 ampere / gram, respectively. Finally, a charge and discharge cycle is performed at a current density of 0.5 ampere / gram to obtain the rate performance data of the tin foil negative electrode material with conductive surface modification of multi-walled carbon nanotubes.
[0070] Example 3
[0071] 2 grams of single-walled carbon nanotubes and 3 grams of sodium carboxymethyl cellulose were placed in a mixing tank, 5 milliliters of deionized water were added, and the mixture was stirred at 2000 rpm for 20 minutes. The slurry was coated on the surface of the prepared 10-micron thick tin foil by a flat film cold roller process. The initial thickness of the slurry was 50 microns, and then transferred to an oven and dried at 80 degrees Celsius for 6 hours to obtain a tin foil negative electrode material with conductive modification on the surface of the single-walled carbon nanotubes. The thickness of the tin foil negative electrode after drying was about 12 microns. Figure 8 The camera-generated photo of the material provided in Example 3 of the present invention is not magnified. Fig. 9 The cross-sectional SEM image of the material is provided for Example 3 of the present invention. Due to the low density of single-walled carbon nanotubes and sodium carboxymethyl cellulose, the mass of the tin foil negative electrode without surface conductivity modification in Comparative Example 1 is almost not significantly increased.
[0072] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig.10 The first cycle charge and discharge curve of the material provided in Example 3 of the present invention is carried out at a voltage range of 0-1 volt and a current density of 0.1 ampere / gram for the first cycle charge and discharge cycle. Fig.11 A specific capacity / coulombic efficiency cycle diagram at different rates of the material is provided for Example 3 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 amps / gram, 0.2 amps / gram, 0.5 amps / gram, and 1 amp / gram, respectively. Finally, a charge and discharge cycle is performed at a current density of 0.5 amps / gram to obtain the rate performance data of the tin foil negative electrode material with conductive surface modification of multi-walled carbon nanotubes. Fig.12 , Fig.13 This is a surface scanning electron microscope (SEM) image of the material after charge and discharge cycles.
[0073] Example 4
[0074] 4 g of graphite and 4 g of sodium alginate were placed in a ball mill, 240 g of ball mill beads were added, 8 ml of a 1:1 mixed solution of deionized water and ethanol were added, and the mixture was stirred at 400 rpm for 1 hour. The slurry and the ball mill beads were separated, and the slurry was coated on the prepared 10-micron thick tin foil surface by a flat film cold roller process. The initial slurry thickness was 30 microns, and then transferred to an oven and dried at 80 degrees Celsius for 6 hours to obtain a tin foil negative electrode material with conductive modification of the graphite surface; the thickness of the tin foil negative electrode after drying was about 12 microns. Due to the low density of graphite and sodium alginate, the mass of the tin foil negative electrode in comparative example 1 that was not surface conductively modified was almost not significantly increased.
[0075] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig.14 The first cycle charge and discharge curve of the material provided for Example 4 of the present invention is carried out at a voltage range of 0-1V and a current density of 0.1A / g for the first cycle charge and discharge cycle. It is seen that the obtained reversible specific capacity is 757 mAh / g, and the first cycle coulombic efficiency is 89.76%. Fig.15 The specific capacity / coulomb efficiency cycle diagram of the material at different rates is provided for Example 4 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 ampere / gram, 0.2 ampere / gram, 0.5 ampere / gram, and 1 ampere / gram, respectively. Finally, the charge and discharge cycle is performed at a current density of 0.5 ampere / gram to obtain the rate performance data of the tin foil negative electrode material with surface conductive modification of multi-walled carbon nanotubes, wherein the reversible specific capacity at a current density of 0.2 ampere / gram is 790 mAh / gram, the reversible specific capacity at a current density of 0.5 ampere / gram is 698 mAh / gram, and the reversible specific capacity at a current density of 1 ampere / gram is 460 mAh / gram. Example 5
[0076] The surface of the prepared 10 micron thick tin foil was modified by the gold plating process. -5 After MPa, gold foil was selected and sprayed with an electric current of 0.5 mA for 100 seconds, transferred to an oven, and dried at 80 degrees Celsius for 2 hours to obtain a tin foil negative electrode material with a gold-plated surface conductively modified. Since the surface spray-plated layer is extremely thin, the thickness and mass of the tin foil negative electrode after drying are almost not significantly increased compared with the tin foil negative electrode in comparative example 1 which has not undergone surface conductive modification.
[0077] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig.16 The first cycle charge and discharge curve of the material provided in Example 5 of the present invention is as follows: the first cycle charge and discharge cycle is carried out at a voltage range of 0-1V and a current density of 0.1A / g to obtain a reversible specific capacity of 766mAh / g, and a first cycle coulombic efficiency of 90.10%. Fig.17 A specific capacity / coulombic efficiency cycle diagram at different rates of the material is provided for Example 5 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 A / g, 0.2 A / g, 0.5 A / g, and 1 A / g, respectively, and finally a charge and discharge cycle is performed at a current density of 0.5 A / g to obtain the rate performance data of the tin foil negative electrode material with a thin spray-coated gold-plated surface conductive modification, wherein the reversible specific capacity at a current density of 0.2 A / g is 810 mAh / g, the reversible specific capacity at a current density of 0.5 A / g is 737 mAh / g, and the reversible specific capacity at a current density of 1 A / g is 518 mAh / g.
[0078] Example 6
[0079] The surface of the prepared 10 micron thick tin foil was modified by the gold plating process. -5 After MPa, gold foil was selected and sprayed with an electric current of 0.5 mA for 300 seconds, transferred to an oven, and dried at 80 degrees Celsius for 2 hours to obtain a tin foil negative electrode material with a gold-plated surface conductively modified. Since the surface spray-plated layer is extremely thin, the thickness and mass of the tin foil negative electrode after drying are almost not significantly increased compared with the tin foil negative electrode in comparative example 1 which has not undergone surface conductive modification.
[0080] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig.18 The first cycle charge and discharge curve of the material provided in Example 6 of the present invention is that the first cycle charge and discharge cycle is carried out at a current density of 0.1 A / g in the voltage range of 0-1 V and the reversible specific capacity is 766 mAh / g, and the first cycle coulombic efficiency is 90.28%. Fig.19 The specific capacity / coulomb efficiency cycle diagram of the material at different rates is provided for Example 6 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 ampere / gram, 0.2 ampere / gram, 0.5 ampere / gram, and 1 ampere / gram, respectively. Finally, the charge and discharge cycle is performed at a current density of 0.5 ampere / gram to obtain the rate performance data of the tin foil negative electrode material with a thick spray-coated gold-plated surface conductive modification, wherein the reversible specific capacity at a current density of 0.2 ampere / gram is 812 mAh / gram, the reversible specific capacity at a current density of 0.5 ampere / gram is 743 mAh / gram, and the reversible specific capacity at a current density of 1 ampere / gram is 555 mAh / gram.
[0081] Example 7
[0082] 2 g of single-walled carbon nanotubes and 3 g of sodium carboxymethyl cellulose were placed in a mixing tank, 6 ml of deionized water were added, and the mixture was stirred at 2000 rpm for 20 minutes. The slurry was coated on the prepared 15-micron thick lead foil surface by a flat film cold roller process, and the initial thickness of the slurry was 60 microns. The slurry was then transferred to an oven and dried at 80 degrees Celsius for 6 hours to obtain a lead foil negative electrode material with surface conductivity modified by single-walled carbon nanotubes. The thickness of the lead foil negative electrode after drying was about 17 microns. Due to the low density of single-walled carbon nanotubes and sodium carboxymethyl cellulose, there was almost no significant increase in the mass of the lead foil negative electrode in comparative example 3 that was not surface conductively modified.
[0083] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig. 20The first cycle charge and discharge curve of the material provided in Example 7 of the present invention is as follows: the first cycle charge and discharge cycle is carried out at a voltage range of 0-1V and a current density of 0.1A / g to obtain a reversible specific capacity of 470mAh / g, and a first cycle coulombic efficiency of 85.79%.
[0084] Comparative Example 1
[0085] The surface of the prepared 10-micron thick tin foil was wiped with anhydrous ethanol to remove impurities attached to the surface, transferred to an oven, and dried at 80 degrees Celsius for 6 hours to obtain a tin foil negative electrode without surface modification. Fig.21 A surface SEM image of the material is provided for Comparative Example 1 of the present invention;
[0086] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig. 22 The first cycle charge and discharge curve of the material is provided for Comparative Example 1 of the present invention. The first cycle charge and discharge cycle is carried out at a current density of 0.1 A / g in a voltage range of 0-1 V. Fig. 22 The charge and discharge curve of the material is provided for comparative example 1 of the present invention. The reversible specific capacity is 736 mAh / g, and the first cycle coulombic efficiency is 87.31%. Fig.23 The specific capacity / coulomb efficiency cycle diagram of the material at different rates is provided for comparative example 1 of the present invention. In the voltage range of 0-1 volt, 10 charge and discharge cycles are performed at 0.1 ampere / gram, 0.2 ampere / gram, 0.5 ampere / gram, 1 ampere / gram, and 2 ampere / gram, respectively. Finally, the charge and discharge cycle is performed at a current density of 1 ampere / gram to obtain the rate performance data of the tin foil negative electrode material without surface conductive modification. Among them, the reversible specific capacity at a current density of 0.2 ampere / gram is 767 mAh / gram, the reversible specific capacity at a current density of 0.5 ampere / gram is 449 mAh / gram, the reversible specific capacity at a current density of 1 ampere / gram is 178 mAh / gram, and the reversible specific capacity at a current density of 2 ampere / gram is 20 mAh / gram. Comparative Example 2
[0087] The surface of the prepared 15-micron thick lead foil was wiped with anhydrous ethanol to remove impurities attached to the surface, transferred to an oven, and dried at 80 degrees Celsius for 6 hours to obtain a lead foil negative electrode without surface modification.
[0088] A button-type half-cell was assembled using metallic sodium as the counter electrode and 1 mol NaPF6-DME as the electrolyte. Glass fiber was used as the separator and a CR2032 button-type cell was assembled in an argon glove box. Fig.24 The first cycle charge and discharge curve of the material is provided for Comparative Example 2 of the present invention. The first cycle charge and discharge cycle is carried out at a current density of 0.1 A / g in a voltage range of 0-1 V. Fig.24The charge and discharge curve of the material is provided for comparative example 3 of the present invention. The reversible specific capacity is 445 mAh / g, and the first cycle coulombic efficiency is 81.51%.
[0089] In the following Table 1, the conductive interface modification process is a flat film cold roller embodiment. The slurry is made by using 2 grams of conductive interface modification material and 3 grams of sodium carboxymethyl cellulose in a stirring tank, adding 5 milliliters of deionized water, stirring and mixing at 2000 rpm for 30 minutes, and the obtained slurry is coated on the surface of the foil by a flat film cold roller process. All electrochemical performance tests of the comparative examples and embodiments in the following table are assembled with button half cells using metallic sodium as the counter electrode and 1 mole of NaPF6-DME as the electrolyte, and glass fiber as the diaphragm, and assembled into CR2032 button cell batteries in an argon glove box. It was carried out at a current density of 0.5 amps / gram in the voltage range of 0-1 volts and room temperature.
[0090]
[0091]
[0092] Table 1
[0093] The conductive interface modified sodium battery alloy foil negative electrode material provided by the embodiment of the present invention. After being treated by a carbon-based conductive material coating or a metal-based conductive material plating process, the conductivity of the foil negative electrode material as a whole can be significantly improved without sacrificing the overall specific capacity of the foil negative electrode, thereby ensuring the capacity under different charge and discharge rates. After a current density of 0.2A / g or above, the specific capacity of the foil negative electrode material after conductive modification is significantly improved compared with the unmodified control sample. The carbon-based conductive material coating or metal-based conductive material plating process used in the conductive modification of the foil negative electrode material of the present invention has a simple process, mature technology, rich choices, low equipment requirements, low overall cost, and easy large-scale preparation.
[0094] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A conductive interface modified sodium battery alloy foil negative electrode material, characterized in that: The conductive interface modified sodium battery alloy foil negative electrode material comprises: a sodium ion battery alloy foil negative electrode and a conductive modification layer completely attached to the bottom surface of the sodium ion battery alloy foil negative electrode; Wherein, the sodium ion battery alloy foil negative electrode is a foil material as a whole, does not contain a conductive agent or a binder inside, and is attached or not attached to a current collector on the surface; The conductive modification layer includes a carbon-based conductive modification layer prepared by a coating process or a metal-based conductive modification layer prepared by a plating process; The mass proportion of the conductive material in the conductive interface modified sodium battery alloy foil negative electrode material is less than 50%.
2. The conductive interface modified sodium battery alloy foil negative electrode material according to claim 1, characterized in that: The sodium ion battery alloy foil negative electrode is specifically: a foil made of a metal element, a foil made of an alloy of multiple metal elements, or a foil made of an alloy of one or more metal elements and one or more non-metallic elements; The metal elements include: one or more of Sn, Sb, Bi, Ge, and Pb elements; the non-metal elements include: one or more of S, Se, and P elements.
3. The conductive interface modified sodium battery alloy foil negative electrode material according to claim 1, characterized in that: The carbon-based conductive modification layer prepared by the coating process includes: one or more of graphene, MXene, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerene, carbon black, Ketjen black, graphite, hard carbon, and soft carbon with conductive properties.
4. The conductive interface modified sodium battery alloy foil negative electrode material according to claim 1, characterized in that: The metal-based conductive modification layer prepared by the plating process includes: one element or a combination of several elements selected from the group consisting of silver (Ag), copper (Cu), gold (Au), aluminum (Al), molybdenum (Mo), tungsten (W), zinc (Zn), cobalt (Co), nickel (Ni), iron (Fe), manganese (Mn) and platinum (Pt) having conductive properties.
5. A method for preparing the conductive interface modified sodium battery alloy foil negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: preparing a conductive modification layer on the bottom surface of a negative electrode of a sodium ion battery alloy foil.
6. The preparation method according to claim 5, characterized in that: The conductive modification layer prepared on the bottom surface of the negative electrode of the alloy foil of the sodium ion battery is: a carbon-based conductive modification layer prepared by a coating process; Specifically, the method comprises: mixing a carbon-based conductive material and a binder according to a required mass ratio, uniformly dispersing the carbon-based conductive material with a solvent, forming a film on the negative electrode surface of a sodium ion battery alloy foil, and drying the dispersed solvent to obtain a surface of a negative electrode of a sodium ion battery alloy foil with a carbon-based conductive modified layer prepared by an attachment coating process and drying the surface; the solid content of the carbon-based conductive material accounts for 20% to 95% by weight; the rotation speed for uniformly dispersing the carbon-based conductive material with a solvent is 500 to 3000 rpm, and the dispersion time is 0.2 to 10 hours; Among them, the specific process of forming the film on the surface of the negative electrode of the sodium ion battery alloy foil includes: one of: flat film cold roller, flat film cold tank, flat film co-extrusion, blown film or blown film co-extrusion.
7. The preparation method according to claim 5, characterized in that: The conductive modification layer prepared on the bottom surface of the negative electrode of the alloy foil of the sodium ion battery is: a metal-based conductive modification layer prepared by a coating process; specifically comprising: subjecting the required metal-based conductive target material to ion bombardment at a set voltage or evaporation and gasification at a set temperature or dissolution through an electrochemical oxidation reaction, and depositing a homogeneous coating on the surface of the negative electrode of the alloy foil of the sodium ion battery, wherein the coating thickness is 10-200 microns; and then drying, the drying temperature is 60-150° C., and the drying time is 4-16 hours; the thickness of the conductive modification layer after drying is 0.5-150 microns; The specific process of preparing the metal-based conductive modification layer by the plating process includes: one of vacuum evaporation, sputtering, spraying, ion plating, electroplating, coating and chemical plating.
8. A sodium ion battery negative electrode, characterized in that: The sodium ion battery negative electrode comprises the conductive interface modified sodium battery alloy foil negative electrode material as described in any one of claims 1 to 4 above.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery negative electrode as described in claim 8 above.
10. An electronic device, characterized in that: The electronic device comprises the sodium ion battery according to claim 9.